The Influence of Work Motivation and Discipline on the Performance of Social Studies Teachers in JHS in Bireuen Regency - Zahara, Zahara; Chairani, Mira; Akbar, Aidil; Syamra, Yesmira; Agustina, Yenni (International Journal of Educational Dynamics, 2024)
This study was motivated by findings on the implementation of the "Merdeka Curriculum" by Social Studies (teachers in Junior High School (JHS) in Bireuen Regency, where performance in teaching and learning responsibilities did not meet expectations. This was evident from the lack of analysis of learning evaluation results and the failure to implement 21st-century framework-based learning, which emphasizes student-centered teaching, critical thinking, and innovation. The research aims to 1) analyze the effect of work motivation on the work discipline of Social Studies teachers in JHS in Bireuen Regency; and 2) examine the combined effects of work motivation and discipline on their performance. The study involved 52 Social Studies teachers in Bireuen Regency, selected using Slovin's formula. Path analysis using SPSS was applied as the analytical technique, and the research employed a causal descriptive approach to investigate direct and indirect relationships between variables. Data were collected through questionnaires distributed to respondents. The findings revealed that 1) work motivation significantly influences the work discipline of Social Studies teachers, indicating that improving teacher motivation enhances their discipline; and 2) work motivation and discipline significantly affect teacher performance, suggesting that enhancing both factors can improve the performance of Social Studies teachers in JHS in Bireuen Regency.